2007
DOI: 10.1007/s10029-007-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

Amyand’s hernia: history, imaging, and management

Abstract: Amyand's hernia can be a challenge for the surgeon. We recommend laparoscopic appendectomy and open repair of the inguinal hernia without using mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 4 publications
0
58
0
3
Order By: Relevance
“…In 1735, Amyand operated on an 11-year-old boy whose inguinal hernia encompassed an inflamed appendix [1]. Of all incarcerated hernias, it has been estimated that only 1 % contain a normal appendix, and most present as did our case with a strangulated right-sided inguinal hernia [1,2]. Even more rare is the presence of appendicitis within the hernia sac at 0.13 % [1].…”
Section: Discussionmentioning
confidence: 94%
“…In 1735, Amyand operated on an 11-year-old boy whose inguinal hernia encompassed an inflamed appendix [1]. Of all incarcerated hernias, it has been estimated that only 1 % contain a normal appendix, and most present as did our case with a strangulated right-sided inguinal hernia [1,2]. Even more rare is the presence of appendicitis within the hernia sac at 0.13 % [1].…”
Section: Discussionmentioning
confidence: 94%
“…Acute appendicitis in an inguinal hernia sac was referred as Amyand's hernia to honour Claudius Amyand, who was the first who described the presence of a perforated appendix within the inguinal hernial sac in 1735 (1)(2)(3)(4)(5)(6)(7). Investigation of anatomic and pathological features of this rare entity in forensic autopsy is important determinants for scientific classification, description also correct pre-postoperative managements and appropriate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Appendix in an inguinal hernia, on the other hand, was first described by the British surgeon Claudius Amyand in 1735 through a case of acute appendicitis in an 11-year-old male patient [3]. It has maintained its position as a rare case with its incidence of 1% since then [4].…”
mentioning
confidence: 99%
“…Güler et al [9] also recently reported 2 cases diagnosed preoperatively by ultrasonography. Abdominal CT is not suggested for all cases of incarcerated inguinal hernia in order to diagnose Amyand's hernia preoperatively, but it should be preferred in selected cases with findings suggesting acute appendicitis alongside incarceration [3]. Diagnostically fever and leukocytosis are not very common [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation